Improved visuospatial neglect after tDCS and computer-assisted cognitive training in Posterior Cortical Atrophy: a single-case study. Issue 1 (2nd January 2021) - Vestito, Lucilla; Trombini, Marco; Mori, Laura; Dellepiane, Silvana; Trompetto, Carlo; Morando, Matteo; Bandini, Fabio
ABSTRACT: Visuospatial neglect (VN) frequently occurs in Posterior Cortical Atrophy (PCA) and requires specific rehabilitation. In this single-case study, we investigated the efficacy of a computer-assisted cognitive training (CCT) alone or coupled with multiple sessions of anodal transcranial direct-current stimulation (A-tDCS) over the right posterior parietal cortex in improving left VN symptoms in a patient with PCA. The digital ReMoVES platform was used for both VN assessment and training. We found a significant improvement after CCT combined with A-tDCS within the limits of a single-case, our results suggest, for the first time, the usefulness of this combined approach in a neurodegenerative disorder.